Bahasa Ciacia Dan Aksara Kontemporernya - Laksono, Kisyani; fendri, yunisse; Indrawati, Dianita (Jurnal Budaya Nusantara, 2017)
The Ciacia language is a regional language in Indonesia that has used Hangul Korean characters since2008. Before using Hangul script, Ciacia language used Wolio script (but later did not match) and then used Hangulscript. Therefore, in the Ciacia language, Hangul characters can be called contemporary charact ers. This paper aims tofind the right script for the language. The method of study is a comparison method. Comparative study of three letters:Wolio, Latin, and Hangul indicate that Latin characters can be used to write the Ciacia language.